When do You Suspect Immune Deficiency in a Child with Eczema? - Rachna S Mohite; Sagar Bhattad (Pediatric Infectious Disease)
Eczematous dermatitis, also known as atopic dermatitis (AD), is a chronic inflammatory skin disease. It globally affects 15–20% of children and 1–3% of adults. Patients with eczema are more prone to develop allergic manifestations like allergic rhinitis, asthma, and 80% usually develop either of them or both. Children and adults with primary immune deficiencies (PIDs) are not only prone to infections, but they develop allergies, autoimmunity, and malignancies also . Eczematous dermatitis is a common finding among several PIDs and many of these patients first present to a dermatologist. Primary immune deficiencies that can present with eczema are hyper-IgE syndrome, Wiskott–Aldrich syndrome, IPEX, etc. Recognizing the warning signs of an underlying PID can help clinicians in the early diagnosis of an underlying immune deficiency. In this paper, we discuss in detail the pathomechanism of eczema in PID and provide a simple approach to PIDs presenting with eczema.